2012
DOI: 10.1377/hlthaff.2011.0329
|View full text |Cite
|
Sign up to set email alerts
|

Direct-To-Consumer Internet Promotion Of Robotic Prostatectomy Exhibits Varying Quality Of Information

Abstract: Robotic surgery to remove a cancerous prostate has become a popular treatment. Internet marketing of this surgery provides an intriguing case study of direct-to-consumer promotions of medical devices, which are more loosely regulated than pharmaceutical promotions. We investigated whether the claims made in online promotions of robotic prostatectomy were consistent with evidence from comparative effectiveness studies. After performing a search and crosssectional analysis of websites that mentioned the procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…22 There is some speculation that this rapid dissemination is, in part, due to successful direct to consumer marketing strategies. 23 While this technology has numerous potential advantages, data from population based comparative effectiveness studies have been mixed. Although men undergoing robotic prostatectomy experience shorter lengths of stay and lower rates of blood transfusions, these patients may be at higher risk for genitourinary complications and salvage therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 There is some speculation that this rapid dissemination is, in part, due to successful direct to consumer marketing strategies. 23 While this technology has numerous potential advantages, data from population based comparative effectiveness studies have been mixed. Although men undergoing robotic prostatectomy experience shorter lengths of stay and lower rates of blood transfusions, these patients may be at higher risk for genitourinary complications and salvage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are avid consumers of information gleaned from the Internet and print media, which often convey the misperception that robotic surgery is superior to alternative treatments. 23 Physicians perceive that newer technology leads to improved quality and, thus, use modern technology to compete for patients. 24 Hospitals compete for patients and providers, which can drive the acquisition of the most up-to-date technologies even if they are not cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of prostate cancer, the benefits of greater magnification in improving the cancer control and functional outcomes from MIRP have been directly advertised to patients. 12 Indeed, several studies support some of these benefits in robotic-assisted surgery, such as shorter LOS and lower risks of perioperative complications. 2,13,14 Other studies have suggested that robotic surgery may be used to increase the market share, as has been previously reported with MIRP in a hospital referral region.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, the average US hospital now spends $1.3 million/yr on advertising and this is the fastest growing form of DTCA . Much of this investment is used to promote their high risk services that are profitable, such as surgical robotics (Jin, Ibrahim et al 2011, Mirkin, Lowrance et al 2012 or oncology (Vater, Donohue et al 2014). Advertising claims made by not-for-profit hospitals about physician services are only subjected to the ethical guidelines of medical and surgical societies (AMA opinion 5.02 1 ; STS advertising policy 2 ) and not regulation by either the FDA or Federal Trade Commission .…”
Section: Introductionmentioning
confidence: 99%